Dendritic Spines: Similarities with Protrusions and Adhesions in Migrating Cells - Vicente-Manzanares, Miguel (2009)
Dendritic spines are specialized, micron-sized post-synaptic compartments that support synaptic function. These actin-based protrusions push the post-synaptic membrane, establish contact with the presynaptic membrane and undergo dynamic changes in morphology during development, as well as in response to synaptic neurotransmission. These processes are propelled by active remodeling of the actin cytoskeleton, which includes polymerization, filament disassembly, and organization of the actin in supramolecular arrays, such as branched networks or bundles. Dendritic spines contain a plethora of adhesion and synaptic receptors, signaling, and cytoskeletal proteins that regulate their formation, maturation and removal. Whereas many of the molecules involved in dendritic spine formation have been identified, their actual roles in spine formation, removal and maturation are not well understood. Using parallels between migrating fibroblasts and dendritic spines, we point to potential mechanisms and approaches for understanding spine development and dynamics.